ANALISA PENGARUH KEPEMILIKAN SAHAM PUBLIK, PROFITABILITAS,LEVERAGE DAN LIKUIDITAS TERHADAP NILAI PERUSAHAAN - Mohamad Nugroho; Astrid Dita Meirina Hakim (Jurnal Akuntansi Bisnis dan Ekonomi (JABE), 2022)
This study aims to determine the effect of Public Share Ownership on Company Value, Profitability on Company Value, Leverage on Company Value, and Liquidity on Company Value in mining companies listed on the Indonesia Stock Exchange for the 2017-2021 Period. Using the Non Probability Sampling technique using the Purposive Sampling method. The population in this study were 44 mining companies listed on the Indonesia Stock Exchange for the 2017- 2021 period and the sample used in this study were 13 mining companies listed on the Indonesia Stock Exchange for the 2017-2021 period. This research was conducted using multiple linear regression methods assisted by the Eviews 10 program and Microsoft Excel 2016. The results showed that Public Share Ownership had no effect on Firm Value, Profitability had no effect on Firm Value, Leverage had no effect on Firm Value, and Liquidity had no effect. to Company Value